2021
DOI: 10.1590/1517-8692202127062021_0034
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Physical Efficiency of Virtual Reality Games in Soccer Players With Low Back Pain

Abstract: Introduction: Virtual reality training (VRT) is an advanced technology that creates virtual games by a computer through specific software. It is a type of rehabilitation training commonly used in balance problems to treat musculoskeletal conditions. Objective: To determine and compare the effects of virtual reality games with those of core stabilization training on physical efficiency in soccer players with chronic low back pain. Methods: A randomized, double-blinded, controlled study was conducted on 60 LBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…This methodology is expected to increase engagement (i.e., perceived usability, experience, immersive tendency, and presence) and provide a context for more goal-directed movements in the rehabilitation program based on the quality of the movement assessment and the game scores. This system's important feature provides real-time feedback, which encourages the player to complete the present game stage and motivates them to go to the following stages quickly [32]. Based on these results, we assume our technological solution for musculoskeletal injury rehabilitation based on VR gaming is a good tool to be used in the context of elite or amateur soccer.…”
Section: Discussionmentioning
confidence: 95%
“…This methodology is expected to increase engagement (i.e., perceived usability, experience, immersive tendency, and presence) and provide a context for more goal-directed movements in the rehabilitation program based on the quality of the movement assessment and the game scores. This system's important feature provides real-time feedback, which encourages the player to complete the present game stage and motivates them to go to the following stages quickly [32]. Based on these results, we assume our technological solution for musculoskeletal injury rehabilitation based on VR gaming is a good tool to be used in the context of elite or amateur soccer.…”
Section: Discussionmentioning
confidence: 95%
“…The duration of a single VR session ranged from 2 to 40 minutes, and the frequency of treatment ranged from 5 to 7 times a week; all the included studies ranged in duration from a single exercise session to 8 weeks. For the control groups, 5 (31%) studies performed conventional balance function training [ 33 , 34 , 38 - 40 ], 5 (31%) performed conventional physical therapy [ 36 , 37 , 41 , 46 , 47 ], 2 (13%) performed core training [ 43 , 44 ], and the remaining conducted treatments, including sham VR [ 32 ], conventional multimodal pain therapy [ 42 ], waiting lists [ 45 ], and standard care [ 35 ]. The intervention details are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…One study reported that after 1 month of intervention, patients experienced nausea and motion sickness [ 32 ], two studies reported that there were no adverse events [ 33 , 37 ], and the remaining studies did not mention adverse events. The overall dropout rate was 4.25% (17/400) in the intervention group and 3.75% (15/400) in the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Virtual Reality games can have beneficial effects on physical recovery following injuries. Virtual Reality game training has been shown to increase clinical and sports performance compared to other training options in soccer players with chronic low back pain [61].…”
Section: Virtual Reality (Vr) Technologymentioning
confidence: 99%